(TRANS) ESTERIFICATION OF MANNOSE CATALYZED BY LIPASE B FROM Candida antarctica IN AN IMPROVED REACTION MEDIUM USING CO-SOLVENTS AND MOLECULAR SIEVE - Nott, K.; Brognaux, A.; Richard, G.; Laurent, P.; Huret, Audrey; Jerome, C.; Blecker, C.; Wathelet, J. P.; Paquot, M.; Deleu, M. (2015)
42